2020
DOI: 10.3892/etm.2020.8753
|View full text |Cite
|
Sign up to set email alerts
|

Efficient detection of differentially methylated regions in the genome of patients with thoracic aortic dissection and association with MMP2 hypermethylation

Abstract: DNA methylation is known to regulate the expression of numerous genes but its role in the pathogenesis of thoracic aortic dissection (TAD) has remained largely elusive. In the present study, the DNA methylome of patients with TAD was analyzed using a methylation microarray and bisulfite pyrosequencing was used to determine whether the hypermethylation of matrix metalloproteinase 2 (MMP2) specifically is associated with TAD. Chip-based whole-DNA methylome analysis was performed on 4 male patients with TAD and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In a zebrafish model, the tet2/3 mutant failed to demethylate genes associated with ECM organization in the endocardium and myocardium, leading to defects in the ECM for cardiogenesis [ 142 ]. Hypermethylated MMP2 was identified and demonstrated to be associated with an increased risk of aortic aneurysm [ 143 ]. More recently, in dilated cardiomyopathy, hypomethylations of MMP-2 and connective tissue growth factor (CTGF) were identified as contributing to heart failure [ 144 ].…”
Section: Epigenetic Regulation Of Ecm In Heartmentioning
confidence: 99%
“…In a zebrafish model, the tet2/3 mutant failed to demethylate genes associated with ECM organization in the endocardium and myocardium, leading to defects in the ECM for cardiogenesis [ 142 ]. Hypermethylated MMP2 was identified and demonstrated to be associated with an increased risk of aortic aneurysm [ 143 ]. More recently, in dilated cardiomyopathy, hypomethylations of MMP-2 and connective tissue growth factor (CTGF) were identified as contributing to heart failure [ 144 ].…”
Section: Epigenetic Regulation Of Ecm In Heartmentioning
confidence: 99%
“…In our previous research, it was found that the protein expression level of DNMT1 and DNMT3B decreased significantly in AAD patients while DNMT3A and DNMTL had the decreased trends with no significance, which indicated the potential role of DNA methylation in AAD[ 17 ]. Several previous studies also paid attention to the DNA methylation changes in AAD[ 18 20 ]. Li N et al detected the DNA methylation in blood samples of TAD patients and found MMP2 promoter hypermethylated[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found in our previous study that the protein expression levels of DNMT1 and DNMT3B decreased significantly in AAD samples while the expression of DNMT3a and DNMTL had the decreased trends with no significance, which indicated the potential role of DNA methylation in AAD[ 17 ]. Most recently, several studies had paid attention to the DNA methylation in AAD[ 18 20 ]. However, the DNA methylation patterns in AAD remain not completely clear.…”
Section: Introductionmentioning
confidence: 99%
“…The hub genes identified in this study were all modified by methylation. Alterations in gene methylation may mediate the involvement of vascular smooth muscle cells and inflammatory cells in the development of aortic dissection [ 24 ]. At present, there are relatively few studies on the regulation of methylation in ATAAD, and we believe that hub genes may be regulated by methylation and thus participate in the progress of ATAAD.…”
Section: Discussionmentioning
confidence: 99%
“…In many cardiovascular diseases, important epigenetic modifications, including methylation, have been shown to affect the development or progression of the disease [ 23 ]. Methylation modification of the gene may serve as a diagnostic and prognostic marker in patients with aortic dissection [ 24 ].…”
Section: Introductionmentioning
confidence: 99%